2020
DOI: 10.28940/terra.v38i4.701
|View full text |Cite
|
Sign up to set email alerts
|

High phosphorus fertilization reduces mycorrhizal colonization and plant biomass of three cultivars of pineapple

Abstract: A strategy to increase the productivity of pineapple agricultural systems is the excessive application of chemical fertilizers. In the state of Veracruz, Mexico, pineapple fields are being fertilized with P (180 to 240 kg ha-1) to maximize yields so that fertilizer applications keep increasing. We assessed the interaction between chemical phosphorus fertilizers, the establishment of mycorrhizal associations and biomass production of Cayenne, Champaka, and MD2 cultivars of pineapple in a greenhouse experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Thus, mycorrhiza's association with pineapple can help water uptake. Pineapple has low P requirements [24], and a high sensitivity to excessive P [25], same as observed in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, mycorrhiza's association with pineapple can help water uptake. Pineapple has low P requirements [24], and a high sensitivity to excessive P [25], same as observed in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Pineapples with the lowest P level were the most significant in terms of plant development and shoot content [23]. In addition, according to [24], the degree of fertiliser in the host plant affects the mycorrhizal activity where, if the P level is higher, the mycorrhizal symbiosis will not occur. It is known that when P availability increases plants do not produce the necessary signals for the establishment of mycorrhizal symbiosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al [ 63 ] found that Pi- deficiency altered the expression of many TFs and Pi-responsive TFs belonging to bHLH or nuclear factor Y (NF-Y) families, showing induction under Pi-sufficient conditions (500 µM KH 2 PO 4 ) or repression with Pi-deficient conditions (0 mM KH 2 PO 4 ) in soybean. It is well known that high Pi concentrations negatively affect the development of arbuscular mycorrhizal symbiosis in plants [ 51 , 64 , 65 ]. However, recent work by Zhang et al [ 66 ] has shown that an HLH domain-containing transcription factor, RiPho4 from R. irregularis, was inhibited in its expression in mycorrhizal roots of Eucalyptus grandis supplied high Pi concentrations (300 and 1000 µM).…”
Section: Discussionmentioning
confidence: 99%
“…The cultivar used influences plant size, nutrient absorption, dry matter production, fruit yield and dry matter accumulation in the different organs of the plant (Hanafi et al, 2009;Neri et al, 2021); which affects the concentration and accumulation of nutrients in each part of the plant (Sampaio et al, 2011;Trejo et al, 2020). Planting density is another factor that can affect the concentration of nutrients because it modifies the size of the plant; as the plantation density increases, the number of leaves emitted, the size of the stem and the size of the fruit are reduced (Cardoso et al, 2013;Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%